(untitled) (The Macau Ricci Institute Journal, 2023)
In early modern times, the Jesuits tried to perform their mission of Evangelization in China from the top down, because their hope was to lead the Chinese emperor to Christianity. He should be followed by his people and finally by the whole Far East, as they hoped, because China was culturally the leading nation (Standaert, 2001, 310). This was part of the method of accommodation that included an indirect mission through science, an apostolate of the press and other things. Important, however, were also images and pictures. Images and pictures played an important role in Europe in Catholicism as a religion of the senses. In the Spiritual Exercises of Ignatius of Loyola, Biblical texts were used for meditation with visualization. During the meditation a mental space was created, which generated an imaginative journey into Biblical narrative, which offered the chance of a spiritual encounter with Biblical persons, scenes and events (Criveller, s.a, 1; Standaert, 2001, 623f). In China, images, xiang 像 or tu 圖 (Criveller, s.a., 3), could help to prepare Non-Christians for Christianity, they could introduce the religion to illiterate people, whereas the new subjects were also attractive for more learned people. Also in China, images served Christians as a catechetical tool, they helped for devotion and meditation. Sometimes, they were even said to have the power to produce miracles (Menegon, 2007, 389f, 399). Pictures were kept more easily in mind than “dry” texts.